Degradation of ester linkages in rice straw components by Sphingobium species recovered from the sea bottom using a non‐secretory tannase‐family α/β hydrolase. (29th June 2021) - Ohta, Yukari; Katsumata, Madoka; Kurosawa, Kanako; Takaki, Yoshihiro; Nishimura, Hiroshi; Watanabe, Takashi; Kasuya, Ken‐ichi
Summary: Microbial decomposition of allochthonous plant components imported into the aquatic environment is one of the vital steps of the carbon cycle on earth. To expand the knowledge of the biodegradation of complex plant materials in aquatic environments, we recovered a sunken wood from the bottom of Otsuchi Bay, situated in northeastern Japan in 2012. We isolated Sphingobium with high ferulic acid esterase activity. The strain, designated as OW59, grew on various aromatic compounds and sugars, occurring naturally in terrestrial plants. A genomic study of the strain suggested its role in degrading hemicelluloses. We identified a gene encoding a non‐secretory tannase‐family α/β hydrolase, which exhibited ferulic acid esterase activity. This enzyme shares the consensus catalytic triad (Ser‐His‐Asp) within the tannase family block X in the ESTHER database. The molecules, which had the same calculated elemental compositions, were produced consistently in both the enzymatic and microbial degradation of rice straw crude extracts. The non‐secretory tannase‐family α/β hydrolase activity may confer an important phenotypic feature on the strain to accelerate plant biomass degradation. Our study provides insights into the underlying biodegradation process of terrestrial plant polymers in aquatic environments.